Difference between revisions of "An Introduction to Mathematical Induction: The Sum of the First n Natural Numbers, Squares and Cubes."
Line 57: | Line 57: | ||
case. In such situations, strong induction assumes that the conjecture is true for ALL cases of lower value than <math style="vertical-align: 0px">n </math> down to our base case. | case. In such situations, strong induction assumes that the conjecture is true for ALL cases of lower value than <math style="vertical-align: 0px">n </math> down to our base case. | ||
− | == The Sum of the first | + | == The Sum of the first ''n'' Natural Numbers == |
− | ''Claim.'' The sum of the first <math style="vertical-align: 0px">n </math> natural numbers is | + | '''''Claim.''''' The sum of the first <math style="vertical-align: 0px">n </math> natural numbers is |
:: <math style="vertical-align: 0px">{\displaystyle \sum_{i=1}^{n}i\,=\,1+2+\cdots+n\,=\,\frac{n(n+1)}{2}.} </math> | :: <math style="vertical-align: 0px">{\displaystyle \sum_{i=1}^{n}i\,=\,1+2+\cdots+n\,=\,\frac{n(n+1)}{2}.} </math> | ||
− | ''Proof.'' We must follow the guidelines shown for induction arguments. | + | '''''Proof.''''' We must follow the guidelines shown for induction arguments. |
Our base step is <math style="vertical-align: 0px">n=1, </math> and plugging in we find that | Our base step is <math style="vertical-align: 0px">n=1, </math> and plugging in we find that | ||
Line 76: | Line 76: | ||
:: <math style="vertical-align: 0px">\begin{array}{rcl} | :: <math style="vertical-align: 0px">\begin{array}{rcl} | ||
− | {\displaystyle \sum_{i=1}^{n}i} & = & {\displaystyle \sum_{i=1}^{n-1}i+n}\\ | + | {\displaystyle \sum_{i=1}^{n}i} & = & {\displaystyle \sum_{i=1}^{n-1}i\,+\,n}\\ |
\\ | \\ | ||
− | & = & {\displaystyle \frac{(n-1)n}{2}+n\qquad\qquad\mbox{(by the induction assumption)}}\\ | + | & = & {\displaystyle \frac{(n-1)n}{2}\,+\,n\qquad\qquad\mbox{(by the induction assumption)}}\\ |
\\ | \\ | ||
− | & = & {\displaystyle \frac{n^{2}-n}{2}+\frac{2n}{2}}\\ | + | & = & {\displaystyle \frac{n^{2}-n}{2}\,+\,\frac{2n}{2}}\\ |
\\ | \\ | ||
& = & {\displaystyle \frac{n^{2}-n+2n}{2}}\\ | & = & {\displaystyle \frac{n^{2}-n+2n}{2}}\\ | ||
Line 91: | Line 91: | ||
as required. | as required. | ||
− | + | <div style="text-align:right;"><math>\square</math></div> | |
== The Sum of the first <math style="vertical-align: 0px">n </math> Squares == | == The Sum of the first <math style="vertical-align: 0px">n </math> Squares == |
Revision as of 21:40, 21 August 2015
Sigma Notation
In math, we frequently deal with large sums. For example, we can write
which is a bit tedious. Alternatively, we may use ellipses to write this as
However, there is an even more powerful shorthand known as sigma notation. When we write
this means the same thing as the previous two mathematical statements. Here, the index below the capital sigma, , is the letter , and the that follows the is our rule to apply to each value of . The values and tell us how many times to repeat the rule, i.e., to follow the rule for then add the rule for then for and continue in this manner until you reach . In other words,
Of course, we can change the rule and/or the index. For example,
Most importantly, we frequently don't have the luxury of bounds that are actual values. We can also write something like
or
These non-fixed indices allow us to find rules for evaluating some important sums.
Proof by (Weak) Induction
When we count with natural or counting numbers (frequently denoted ), we begin with one, then keep adding one unit at a time to get the next natural number. In other words,
This is the basis for weak, or simple induction; we must first prove our conjecture is true for the lowest value (such as ), and then show whenever it's true for an arbitrary it's true for as well. This mimics our development of the natural numbers.
It is also equivalent to prove that whenever the conjecture is true for it's true for Which approach you choose can depend on which is more convenient, or frequently which is more appealing to the teacher grading the work.
Although we won't show examples here, there are induction proofs that require strong induction. This occurs when proving it for the case requires assuming more than just the case. In such situations, strong induction assumes that the conjecture is true for ALL cases of lower value than down to our base case.
The Sum of the first n Natural Numbers
Claim. The sum of the first natural numbers is
Proof. We must follow the guidelines shown for induction arguments. Our base step is and plugging in we find that
This gives us our starting point. For the induction step, let's assume the claim is true for so
Now, we have
as required.
The Sum of the first Squares
Claim. The sum of the first squares is
Proof. Again, our base step is and plugging in we find that
This gives us our starting point. For the induction step, let's assume the claim is true for so
Now, we have
as required.
The Sum of the first Cubes
Claim. The sum of the first cubes is
Notice that the formula is really similar to that for the first natural numbers.
Proof.. Plugging in we find that
completing our base step.
For the induction step, let's assume the claim is true for so
Now, we have
as required.
Aside from being good examples of simple or weak induction, these formulas are frequently used to find an integral as a limit of a Riemann sum. \end{document}